REALISME MAGIS SEBAGAI REPRESENTASI KRITIK KEADAAN DALAM MANUSIA KELELAWAR KARYA DAMHURI MUHAMMAD - Salma Dhiya Ulhaq (Jurnal Ilmiah SEMANTIKA, 2023)
Indonesian people are one of many eastern countries that still believe in the tradition of honoring their ancestors, therefore people still believe in mystical things. This has led some writers to use people's 'trust' in mysticism in their literary works. This article provides insight into how Wendy B. Faris' magical realism theory can be applied in the analysis of fictional stories. by analyzing magical realism in the selected short story by Kompas, “Bat Man” Damhuri Muhammad in 2022, through magical realism elements; (a) irreducible elements; (b) world phenomenal; (c) dimensions of the amalgamation; (d) unsetting doubts; and (e) disruption of time, space and identity in short stories. The five seek to establish a connection between real and magical life through the boundaries between the elements that have been broken. The use of this theory helps broaden the understanding of magical realism as a literary approach that allows social criticism through magical representations of complex social situations. The results of the study found that the 'bat man' who died horribly in this story represents the situation towards the hunting of bats that caused the spread of the virus, showing the arrogance of humans who seem to be brutal towards other living things. Keywords: Critique of Circumstances; Bat-Man; Magical Realism; Wendy B. Farris